Leaf epidermal investigations on Festuca pratensis Huds. subspecies - Dani, Magdolna; Kovács, J. Attila (Acta Biologica Szegediensis, 2011)
This work deals with the examination of the leaf epidermal anatomy of two subspecies of Meadow fescue: Festuca pratensis Huds.: subsp. pratensis and subsp. apennina. As a result of our studies carried out on Central European natural populations of different origin, it can be concluded that in the case of both microtaxa, in all the examined populations the upper and lower epidermis exhibits structural differences. The variation between the populations manifest in the differences in dimensions of certain cells of the epidermis, in the size and amount of silica cells, hairiness, and the size of the bristles. The difference of the two subspecies on the basis of epidermal structure is the length of stoma complexes, the number and dimension of bristles as well as the length of the epidermis cells.